Mild and efficient synthesis of trans-3-aryl-2-nitro-2, 3-dihydrobenzofurans on water. (8th July 2020) - Feng, Juhua; Wang, Siyuan; Feng, Jinxiang; Li, Qiuju; Yue, Junping; Yue, Guizhou; Zou, Ping; Wang, Guangtu
Abstract : A protocol to prepare trans -3-aryl-2-nitro-2, 3-dihydrobenzofurans has been developed on water. The protocol avoids the use of toxic solvents, tedious work-up procedures, and chromatographic separation. Abstract : An environmental-friendly and mild method has been successfully developed for the synthesis of 3-aryl-2-nitro-2, 3-dihydrobenzofurans through domino Friedel–Crafts/substitution reaction of ( Z )-bromonitrostyrenes with sesamol. A variety of substrates performed well in this reaction, and the corresponding 3-aryl-2-nitro-2, 3-dihydrobenzofurans were obtained in excellent yields (up to 99%). Significantly, water served as the sole green solvent. Remarkably, the crude products were purified by simple filtration, washing with water and drying in oven without any organic solvents or silica gel.